STUDY OF THE NUCLEATION AND GROWTH OF CESIUM IODIDE AND CESIUM CHLORIDE ON CESIUM IODIDE SUBSTRATES - Muhammad, Jan (Journal of Research (Science), 2004)
Single crystals of cesium iodide with reasonable flat surfaces are produced in the holes of carbon film and have been used as substrates. Lattice structure of cesium iodide with its diffraction patterns has been discussed. Two kinds of experiments have been carried out. In the first, the film of CsI and CsCl grown by evaporation was transferred into the electron microscope without exposing it to the atmosphere, by means of transport chamber. In the second type of experiments the grown film was exposed to the atmosphere before being observed in the electron microscope. The micrographs and diffraction patterns of overgrowth together with substrate reveal that unexposed deposits of CsI on CsI do not show any orientation. Exposed deposits are well oriented with simple cubic lattice structure, indicating poor homo-epitaxy from the vapor but good epitaxial growth from solution. Unexposed and exposed deposits of CsCl on CsI are well oriented in all cases with there axes parallel to those of the substrate.